Remarks on Receiving the 2003 Public Service Award - Raymond D. Rawson, DDS, MA (Blackwell Synergy, 2003)
I would like to convey my heartfelt gratitude to the American Association of Public Health Dentistry for conferring the National Public Service Award on me. The prestige and deep significance this award imparts both humble and honor me.